Proposal of a conditioning activity model on sprint swimming performance - Botta de Arruda, T.; Barbieri, R. A.; Luiz de Andrade, V.; Cursiol, J. A.; Kalva-Filho, C. A.; Rodrigues Bertucci, D.; Papoti, M. (Frontiers in Physiology, 2020)
This study aimed to propose a conditioning activity (CA) model to stimulate improvement on neuromuscular responses, mechanical parameters and for the 50-m freestyle swimming. Thirteen male swimmers (19 ± 3 years and performances of 77% in relation to World Championship records) performed four CA protocols followed by a maximum performance in the 50-m freestyle. In the first protocol (P1) swimmers performed a standard warm-up (~15 min); in the second protocol (P2) lunges (3 × 85% of the one-repetition maximum); in the third (P3) pull-ups (3 maximum repetitions) and box jumps 40 cm high and 60 cm deep (1 × 5 with 10% of the corporal weight); and in the fourth protocol (P4) a combination of exercises from the second and third protocols. CA protocols had no effect on the standard warm-up. However, P2 performance (27.01 ± 1.25 s) was similar to P1 (27.01 ± 1.18 s) and presented higher positive effects in mechanical parameters for the swim start performance in comparison to other protocols, contributing to improvements in the 50-m freestyle. In addition, turnaround time also had a negative effect, mainly in P3 (3.12 ± 0.28 s), signaling the improvement of this variable in all protocols (P1: 3.30 ± 0.38 s; P2: 3.17 ± 0.30 s; P4: 3.17 ± 0.34 s). P2 (after: 80 ± 11%; before: 82.7 ± 9.9%) and P3 (after: 82.7 ± 9.9%; before: 85.1 ± 9.7%) presented a possible positive effect on the percentage of voluntary activation in relation to P1 (after: 79.3 ± 10.7%; before: 76.3 ± 12%). In conclusion, the proposed conditioning activity protocols were not efficient for performance improvement in the 50-m freestyle compared to the standard model and seem to specifically influence each phase of the event.